Green Synthesis of Pyrrole Derivatives - Portilla Zúñiga, Omar Miguel (2017)
Pyrroles are organic cyclic compounds with an extensive and fascinating chemistry. These compounds have a wide structural variety and are an important basis in technological development as they can be used as drugs, dyes, catalysts, pesticides, etc. Therefore, the production of these heterocyclic compounds by efficient clean methodologies is a great achievement in contemporary chemistry. In this paper, we show recent green procedures in the synthesis of pyrrole derivatives, such as Hantzsch, Knorr and Paal-Knorr syntheses, as well as new eco-friendly synthetic procedures with high efficiency and low environmental impact.